Chronic social defeat stress causes retinal vascular dysfunction. (December 2021) - Wang, Maoren; Milic, Marija; Gericke, Adrian; Mercieca, Karl; Liu, Hanhan; Ruan, Yue; Jiang, Subao; van Beers, Tim; von Pein, Harald D.; Müller, Marianne B.; Prokosch, Verena
Abstract: Purpose: The roles of vascular dysfunction and chronic stress have been extensively discussed in the pathophysiology of glaucoma. Our aim was to test whether chronic stress causes retinal vascular dysfunction and therewith induces retinal ganglion cells (RGCs) loss. Methods: Twelve mice underwent chronic social defeat (CSD) stress, while 12 mice received control treatment only. Intraocular pressure (IOP) was measured with a rebound tonometer. Blood plasma corticosterone concentration and adrenal gland weight were used to assess stress levels. Brn-3a staining in retinas and PPD staining in optic nerve cross sections were conducted to assess the survival of RGCs and axons respectively. The ET-1 and α-SMA levels were determined in retina. Retinal vascular autoregulation, functional response to various vasoactive agents and vascular mechanics were measured using video microscopy. Results: No significant difference in IOP levels was observed during and after CSD between CSD mice and controls. CSD stress caused hypercortisolemia 2 days post-CSD. However, increased corticosterone levels went back to normal 8 months after CSD. CSD-exposed mice developed adrenal hyperplasia 3 days post-CSD, which was normalized by 8 months. RGC and axon survival were similar between CSD mice and controls. However, CSD stress caused irreversible, impaired autoregulation and vascular dysfunction of retinal arterioles in CSD mice. In addition, impaired maximal dilator capacity of retinal arterioles was observed 8 months post-CSD rather than 3 days post-CSD. Remarkably, ET-1 levels were increased 3 days post-CSD while α-SMA levels were decreased 8 months post-CSD. Conclusions: We found that CSD stress does not cause IOP elevation, nor loss of RGCs and their axons. However, it strikingly causes irreversible impaired autoregulation and endothelial function in murine retinal arterioles. In addition, CSD changed vascular mechanics on a long-term basis. Increased ET-1 levels and loss of pericytes in retina vessels may involve in this process. Highlights: Mental stress did not increase intraocular pressure. Mental stress did not cause neuronal degeneration of retina and optic nerve. Mental stress caused impaired autoregulation of retinal arterioles. Mental stress caused vascular dysfunction of retinal arterioles. Mental stress changed vascular mechanics on a long-term basis.